Pharmacological and Non-Pharmacological Recanalization Strategies in Acute Ischemic Stroke - Frendl, Anita; Csiba, László (Frontiers in Neurology, 2011)
According to the guidelines of the European Stroke Organization (ESO) and the American Stroke Association (ASA), acute stroke patients should be managed at stroke units that include well organized pre- and in-hospital care. In ischemic stroke the restoration of blood flow has to occur within a limited time window that is accomplished by fibrinolytic therapy. Newer generation thrombolytic agents (alteplase, pro-urokinase, reteplase, tenecteplase, desmoteplase) have shorter half-life and are more fibrin specific. Only alteplase has FDA approval for the treatment of acute stroke (1996). The NINDS trial proved that alteplase was effective in all subtypes of ischemic strokes within the first 3 hours. In the ECASS-III trial, intravenous alteplase therapy was found to be safe and effective (with some restrictions) if applied within the first 3-4.5 hours. In middle cerebral artery (MCA) occlusion additional transcranial Doppler insonication may improve the breakdown of the blood clot. According to the ESO and ASA guidelines, intra-arterial thrombolysis is an option for recanalisation within 6 hours of MCA occlusion. Further trials on the intra-arterial (IA) therapy are needed, as previous studies have involved relatively small number of patients (compared to IV. trials) and the optimal intra-arterial dose of alteplase has not been determined (20-30 mg is used most commonly in 2 hours). Patients undergoing combined (IV+IA) thrombolysis had significantly better outcome than the placebo group or the IV therapy alone in the NINDS Trial (IMS Trials). If thrombolysis fails or it is contraindicated, mechanical devices (e.g. MERCI- FDA approved in 2004) might be used to remove the occluding clot. Stenting can also be an option in case of acute internal carotid artery occlusion in the future. An intra-aortic balloon was used to increase the collateral blood flow in the SENTIS trial (results are under evaluation). Currently, there is no approved effective neuroprotective drug.